The involvement of parents in healthcare decisions where adult children are at risk of lacking decision‐making capacity: a qualitative study of treatment decisions in epilepsy. (25th April 2012) - Redley, M.; Prince, E.; Bateman, N.; Pennington, M.; Wood, N.; Croudace, T.; Ring, H.
Abstract Background Patients with intellectual disabilities (ID) receive health care by proxy. It is family members and/or paid support staff who must recognise health problems, communicate with clinicians, and report the benefits, if any, of a particular treatment. At the same time international and national statutes protect and promote the right of people with disabilities to access the highest attainable standards of health on the basis of free and informed consent. Methods To consider the role of parent‐proxies in the management of epilepsy in adult children with ID who are at risk of lacking capacity to make decisions about their health care we interviewed 21 mothers. Findings These mothers are not pursuing changes in treatment that might improve their son or daughter's epilepsy, nor are they willing to countenance changes in treatment. Clinicians concerned to build and sustain therapeutic alliances with these mothers, our evidence suggests, may well avoid going against their wishes. Discussion Our research highlights the interactional contingencies of a hitherto neglected three‐way clinical relationship comprising parent‐proxy, an adult at risk of lacking decision‐making capacity, and a treating clinician. This is a relationship, our findings suggest, where little importance is attached to either patient consent, or involvement in treatment decisions.